The message of Leviticus : free to be holy - Tidball, Derek (Downers Grove, IL : InterVarsity Press, 2005)
"Derek Tidball explores the picture in Leviticus of Israel being brought together under the law of Moses.
Consecration to God : the burnt offering (1:1-17) -- A gift for God : the grain offering (2:1-16) -- Fellowship with God : the peace offering (3:1-17) -- Forgiveness from God : the sin offering (4:1-5:13) -- Amendment before God : the guilt offering (5:14-6:7) -- Instructed by God : the priests' responsibilities (6:8-7:38) -- Anointed for service (8:1-36) -- The glory of the Lord appeared (9:1-24) -- Fire from Lord (10:1-20) -- Purity and the diet (11:1-47) -- Purity and the body (12:1-8, 15:1-33) -- Purity and disease (13:1-14:57) -- For all the sins of Israel (16:1-34) -- God's word about life blood (17:1-16) -- God's word about family health (18:1-30) -- God's word about society's welfare (19:1-37) -- God's word about the penal code (20:1-27) -- God's word about spiritual leadership (21:1-22:33) -- God's word about times of celebration (23:1-44) -- God's word about safeguarding the sacred (24:1-23) -- God's word about radical economics (25:1-55) -- God's word about future prosperity (26:1-46) -- God's word about consecration (27:1-34).
Includes bibliographical references.
Keywords: Bible. -- Commentaries